A novel tube placement technique in EUS‐guided drainage for small pancreatic pseudocyst: Spinning lasso method. (14th September 2022) - Nagai, Kazumasa; Itoi, Takao; Mukai, Shuntaro; Tsuchiya, Takayoshi; Ishii, Kentaro; Tonozuka, Ryosuke; Matsunami, Yukitoshi; Nakatsubo, Ryosuke; Joyama, Eri; Sofuni, Atsushi
Abstract : This paper discusses a novel tube placement technique; the "spinning lasso method", in EUS‐guided drainage for small pancreatic pseudocysts (PC) with video. In general, the placement of a drainage tube can be difficult in a small PC and the tube often deviates during attempted insertions into the cavity. The technique helps to mitigate this problem.